Simultaneous Determination of 16 Chemical Constituents in the Traditional Chinese Medicinal Prescription Si-Ni-San and Chaihu-Shugan-San by Ultra Performance Liquid Chromatography Coupled with Photodiode Array Detection - Qiu, Xin-Jian; Huang, Xi; Chena, Ze-Qi; Ren, Ping (Asian Journal of Chemistry, 2011)
A simple, rapid and sensitive ultra performance liquid chromatography (UPLC) coupled with photodiode array (PDA) detection method was established for the simultaneous determination of 16 components in two traditional Chinese medicines viz., Si-Ni-San (SNS) and Chaihu-Shugan- San (CSS) i.e., gallic acid, oxypaeoniflora, albiflorin, paeoniflorin, liquiritin, benzoic acid, narirutin, naringin, hesperidin, neohesperidin, meranzin hydrate, liquiritigenin, quercimelin, benzoylpaeoniflorin, isoliquiritigenin and formononetin. These were separated in less than 18 min using an Acquity BEH C18 column (100 mm × 2.1 mm i.d. 1.7 μM). The mobile phase comprising acetonitrile (A) and 0.5 % acetic acid (B) was used to elute the targets in gradient elution mode. All calibration curves showed good linear regression (R2 ≤ 0.9992) within the test ranges. Inter- and intra-day precisions for all investigated components expressed as relative standard deviation (RSD) ranged from 1.86-6.02 %. Recoveries ranged from 90.31-104.05 % with RSD ≤ 4.5 %. The proposed method was validated for specificity, accuracy, precision and limits of detection. The method was successfully applied to determine the contents of 16 components in SNS and CSS.